The Compression of Perceived Time in a Hot Environment Depends on Physiological and Psychological Factors. Issue 1 (January 2014) - Tamm, Maria; Jakobson, Ainika; Havik, Merle; Burk, Andres; Timpmann, Saima; Allik, Jüri; Ööpik, Vahur; Kreegipuu, Kairi
The human perception of time was observed under extremely hot conditions. Young healthy men performed a time production task repeatedly in 4 experimental trials in either a temperate (22 °C, relative humidity 35%) or a hot (42 °C, relative humidity 18%) environment and with or without a moderate-intensity treadmill exercise. Within 1 hour, the produced durations indicated a significant compression of short intervals (0.5 to 10 s) in the combination of exercising and high ambient temperature, while neither variable/condition alone was enough to yield the effect. Temporal judgement was analysed in relation to different indicators of arousal, such as critical flicker frequency (CFF), core temperature, heart rate, and subjective ratings of fatigue and exertion. The arousal-sensitive internal clock model (originally proposed by Treisman) is used to explain the temporal compression while exercising in heat. As a result, we suggest that the psychological response to heat stress, the more precisely perceived fatigue, is important in describing the relationship between core temperature and time perception. Temporal compression is related to higher core temperature, but only if a certain level of perceived fatigue is accounted for, implying the existence of a thermoemotional internal clock.